Peran Komunikasi Politik Elit Tradisional dalam Konstalasi Politik Lokal - Rumalutur, Faisal Idris (Jurnal Inovasi Komunikasi, 2024)
Direct regional head elections (PILKADA) are one of the advances in democracy in Indonesia. Previous PILKADA, which were conducted through legislative bodies, were felt to not directly reflect the wishes of the people as constituents. However, direct democracy at the local level has, on the one hand, strengthened the traditional social order that has existed in society since the beginning. These old relationships are used by traditional political elites to win political succession in the region. The simultaneous direct PILKADA in East Seram Regency in 2015 showed how these old or traditional social relationships are used as tools and media for political communication.